2022
DOI: 10.1111/1753-6405.13229
|View full text |Cite
|
Sign up to set email alerts
|

Scope and quality of economic evaluations of Aboriginal and Torres Strait Islander health programs: a systematic review

Abstract: Objectives: Identify the number, type, scope and quality of economic evaluations of Aboriginal and Torres Strait Islander health programs. Methods:A systematic review of peer-reviewed and grey literature was conducted for articles published from 2010 to 2020 that reported a full economic evaluation of Aboriginal and Torres Strait Islander health programs. Data extraction included: type of economic evaluation, comparators, data sources and concerns, and outcome measures. Methodological quality was assessed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A recent systematic review identified that more than 90% of First Nations-specific programs in Australia were not evaluated let alone evaluated for their cost-effectiveness. 30 We are aware that out-of-pocket expenses and productivity loss costs are based on a smaller proportion of the total study population. Nevertheless, our study is the first in the world to explore this cost for First Nations families.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review identified that more than 90% of First Nations-specific programs in Australia were not evaluated let alone evaluated for their cost-effectiveness. 30 We are aware that out-of-pocket expenses and productivity loss costs are based on a smaller proportion of the total study population. Nevertheless, our study is the first in the world to explore this cost for First Nations families.…”
Section: Discussionmentioning
confidence: 99%